CRITERIA FOR A COMPRAVISTIC ANALYSIS IN WORKS OF TRANSLATION FROM UZBEK TO ENGLISH (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the criteria for conducting a comparative analysis of translations from Uzbek to English, addressing linguistic, cultural, and stylistic challenges. It reviews existing literature, proposes a methodological framework, and discusses findings from sample translations. The study emphasizes the importance of fidelity, cultural equivalence, and stylistic appropriateness in evaluating translation quality. Suggestions for future research and practical applications are provided to enhance translation practices in this language pair.